Repotting the Geraniums: On Nested Graph Transformation Rules - Rensink, Arend; Kuperus, Jan-Hendrik (Electronic Communications of the EASST, 2009)
We propose a scheme for rule amalgamation based on nested graph predicates. Essentially, we extend all the graphs in such a predicate with right hand sides. Whenever such an enriched nested predicate matches (i.e., is satisfied by) a givenhost graph, this results in many individual match morphisms, and thus many âsmallâ rule applications. The total effect is described by the amalgamated rule. This makes for a smooth, uniform and very powerful amalgamation scheme, which we demonstrateon a number of examples. Among the examples is the following, which we believe to be inexpressible in very few other parallel rule formalism proposed in the literature: repot all flowering geraniums whose pots have cracked.